Dr YSRHU Year of Banana 2022-23 (Current Horticulture, 2024)
Dr YSR Horticultural University, Venkataramanna gudem, Andhra Pradesh, is taking up many new initiatives focusing over all development of able horticultural in crops Andhra Pradesh. With the initiative of Dr T Janakiram, Vice-Chancellor, Sri Kakani Govardhan Reddy garu, Hon'ble Minister for Agriculture, Cooperation, Marketing & Food Processing, Government of Andhra Pradesh announced the year 2022-23 as 'Dr YSRHU Year of Banana 2022- 23' with the released of the Logo on 20 October 2022. Under this, the university proposes to take up following activities targeting all the stakeholders in Andhra Pradesh